0
$\begingroup$

Use Orthogonal rewriting of multi-vectors to verify $(a \land b \land c)$$(d \land e)$ where a,b,c,d,e are vectors in a dimension of at least 5?
Note: by definition the grade $\vert r-s \vert$ vector of $A_r$ $B_s$ is $A_r$ $\cdot$ $B_s$

I know that you can use the geometric product of an r-vector($A_r$ i.e., a vector of grade r) and a s-vector ($B_s$) is a sum of multi-vectors whose lowest grade is $\vert r-s \vert$ and highest grade is $\vert r+s \vert$. I need help in determining the how to verify the multi-vectors. I am new to multi-vectors

$\endgroup$
  • $\begingroup$ Are you translating these questions from another language? Your last couple haven't used the standard terminology and this one I can't even decipher. I have no idea what it means to "verify" a multivector and only a guess as to how to "use orthogonal rewriting". $\endgroup$ – user137731 Jul 21 '16 at 4:40
  • $\begingroup$ For example, r-vector $a_1 \land ... \land a_r$ = $a_1 ' \land ... \land a_r '$ where the latter vectors $a_1 ',...,a_r '$ are orthogonal vectors $\endgroup$ – Zman Jul 21 '16 at 4:57
  • $\begingroup$ this question is confusing to me also $\endgroup$ – Zman Jul 21 '16 at 4:58
0
$\begingroup$

As with one of your commenters, I don't know what you mean by orthogaonal rewriting, nor verify.

I can only guess that by verify you mean to expand the product in terms of it's component grades. That expansion takes the form

$$\begin{aligned}\left( { a \wedge b \wedge c } \right) \left( { d \wedge e } \right)&=\left( { a \wedge b \wedge c } \right) \cdot \left( { d \wedge e } \right) \\ &+{\left\langle{{ \left( { a \wedge b \wedge c } \right) \left( { d \wedge e } \right) }}\right\rangle}_{3} \\ &+a \wedge b \wedge c \wedge d \wedge e \end{aligned}$$

The first term is a vector and expands as

$$\begin{aligned}\left( { a \wedge b \wedge c } \right) \cdot \left( { d \wedge e } \right)&=\left( { \left( { a \wedge b \wedge c } \right) \cdot d } \right) \cdot e \\ &=\left( { a \wedge b (c \cdot d) +b \wedge c (a \cdot d) +c \wedge a (b \cdot d) } \right) \cdot e \\ &= a (b \cdot e) (c \cdot d) +b (c \cdot e) (a \cdot d) +c (a \cdot e) (b \cdot d) \\ &-(a\cdot e) b (c \cdot d) -(b\cdot e) c (a \cdot d) -(c\cdot e) a (b \cdot d) \\ &= a \left( { (b \cdot e) (c \cdot d) -(c\cdot e) (b \cdot d) } \right) \\ &+b \left( { (c \cdot e) (a \cdot d) -(a\cdot e) (c \cdot d) } \right) \\ &+c \left( { (a \cdot e) (b \cdot d) -(b\cdot e) (a \cdot d) } \right).\end{aligned}$$

The second term is a trivector and expands as

$$\begin{aligned}2 {\left\langle{{ \left( { a \wedge b \wedge c } \right) \left( { d \wedge e } \right) }}\right\rangle}_{3}&={\left\langle{{ \left( { a \wedge b \wedge c } \right) (d e - e d)}}\right\rangle}_{3} \\ &={\left\langle{{ \left( { a \wedge b \wedge c } \right) d e -\left( { a \wedge b \wedge c } \right) e d}}\right\rangle}_{3} \\ &={\left\langle{{ \left( { a \wedge b \wedge c \wedge d } \right) e +\left( { \left( { a \wedge b \wedge c } \right) \cdot d } \right) e }}\right\rangle}_{3} \\ &-{\left\langle{{ \left( { a \wedge b \wedge c \wedge e } \right) d+\left( {\left( { a \wedge b \wedge c } \right) \cdot e } \right) d}}\right\rangle}_{3} \\ &= \left( { a \wedge b \wedge c \wedge d } \right) \cdot e + \left( { \left( { a \wedge b \wedge c } \right) \cdot d } \right) \wedge e \\ &- \left( { a \wedge b \wedge c \wedge e } \right) \cdot d- \left( {\left( { a \wedge b \wedge c } \right) \cdot e } \right) \wedge d \\ &= \left( { a \wedge b \wedge c } \right) d \cdot e - \left( { a \wedge b \wedge d } \right) c \cdot e \\ &+ \left( { a \wedge c \wedge d } \right) b \cdot e - \left( { b \wedge c \wedge d } \right) a \cdot e \\ &+ \left( { a \wedge b \wedge e } \right) c \cdot d - \left( { a \wedge c \wedge e } \right) b \cdot d + \left( { b \wedge c \wedge e } \right) a \cdot d \\ &- \left( { a \wedge b \wedge c } \right) e \cdot d + \left( { a \wedge b \wedge e } \right) c \cdot d \\ &- \left( { a \wedge c \wedge e } \right) b \cdot d + \left( { b \wedge c \wedge e } \right) a \cdot d \\ &- \left( { a \wedge b \wedge d } \right) c \cdot e + \left( { a \wedge c \wedge d } \right) b \cdot e - \left( { b \wedge c \wedge d } \right) a \cdot e \\ &= - 2 \left( { a \wedge b \wedge d } \right) c \cdot e + 2 \left( { a \wedge c \wedge d } \right) b \cdot e \\ &- 2 \left( { b \wedge c \wedge d } \right) a \cdot e + 2 \left( { a \wedge b \wedge e } \right) c \cdot d \\ &- 2 \left( { a \wedge c \wedge e } \right) b \cdot d + 2 \left( { b \wedge c \wedge e } \right) a \cdot d.\end{aligned}$$

Putting all the pieces together, assuming no algebra errors (this is really a task better suited for a computer algebra system), the multivector product expands as

$$\begin{aligned}\left( { a \wedge b \wedge c } \right) \left( { d \wedge e } \right)&= a \left( { (b \cdot e) (c \cdot d) -(c\cdot e) (b \cdot d) } \right) \\ &+b \left( { (c \cdot e) (a \cdot d) -(a\cdot e) (c \cdot d) } \right) \\ &+c \left( { (a \cdot e) (b \cdot d) -(b\cdot e) (a \cdot d) } \right) \\ &- \left( { a \wedge b \wedge d } \right) c \cdot e + \left( { a \wedge c \wedge d } \right) b \cdot e \\ &- \left( { b \wedge c \wedge d } \right) a \cdot e + \left( { a \wedge b \wedge e } \right) c \cdot d \\ &- \left( { a \wedge c \wedge e } \right) b \cdot d + \left( { b \wedge c \wedge e } \right) a \cdot d \\ &+a \wedge b \wedge c \wedge d \wedge e \end{aligned}$$

$\endgroup$
0
$\begingroup$

For computer algebra method look at the bac_cab section of -

http://github.com/brombo/galgebra/blob/master/examples/LaTeX/latex_check.pdf

The galgebra modules (python) are at -

http://github.com/brombo/galgebra

If you are interested read the doc first.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.